Fluorescent visualization of oxytocin in the hypothalamo-neurohypophysial system - Hashimoto, Hirofumi; Matsuura, Takanori; Ueta, Yoichi (Frontiers in Neuroscience, 2014)
Oxytocin (OXT) is well known for its ability to the milk ejection reflex and uterine contraction. It is also involved in several other behaviors, such as anti-nociception, anxiety, feeding, social recognition and stress responses. OXT is synthesized in the magnocellular neurosecretory cells (MNCs) in the hypothalamic paraventricular (PVN) and the supraoptic nuclei (SON) that terminate their axons in the posterior pituitary (PP). We generated transgenic rats that express the OXT and fluorescent protein fusion gene in order to visualize oxytocin in the hypothalamo-neurohypophysial system. In these transgenic rats, fluorescent proteins were observed in the MNCs and axon terminals in the PP. This transgenic rat is a new tool to study the physiological role of OXT in the hypothalamo-neurohypophysial system.